Code Mixing Practice: A Solution to Increase Learners ' Self-Confidence in English Learning - Muhammad Wahid (Jurnal Indonesia Sosial Sains, 2024)
This research aims to describe code-mixing as a means of conversation for students to increase self-confidence. This research focuses on the code-mixing between English, Indonesian, and Manado used by grade 11 students of Linguistics at SMA Negeri 7 Manado to increase self-confidence. This research method uses qualitative research with data collection instruments, such as observation and interviews. The results of this study show that it finds a reason similar to Hoffman's theory. The reasons include talking about a specific topic, quoting other people's words, repetition for clarification, and clarifying the intent of the conversation to the interlocutor. The study also found additional reasons: lack of vocabulary and fear of using the wrong sentences. Students realize they will feel more confident speaking when the teacher allows them to code-mix.